Estudio de prefactibilidad para la instalación de una planta de producción de botellas fabricadas con un polímero biodegradable - Griebenow Almonte, Camila B (2020)
The purpose of this work is to evaluate the prefeasibility of the installation of a bottle producing plant from a biodegradable polymer, establishing its technical, economic, market and social viability, considering a great opportunity in plastics industry. We analyze the apparent internal demand and its behavior in recent years. Then, we apply the survey method for companies in order to obtain the demand for our project. Through location techniques such as the ranking factors and the Brown & Gibson method, we chose the right place for the location of our plant. We determine the size of the plant considering many factors to establish the minimum and maximum size. Subsequently, we made the analysis of the plant capacity, define the production process, choose the appropriate machinery for our project, define the quality and safety procedures, design our own supply chain and, finally, define the physical distribution of our project across the plane to corroborate the technical feasibility. The type of company to be established and the detailed organization chart of the staff and their functions within the company were also defined. Finally, we propose the economic and financial analysis of the project, having favorable results after evaluating the investment, loans, defining our budget and Financial Statements, analyzing the indicators and evaluating the ratios, as well as socially evaluating our project.